Catecholamine metabolite excretion in spina bifida - McKibbin, B. (1969)
The urinary excretion of vanilmandelic acid (VMA), homovanillic acid (HVA), and parahydroxyphenylacetic acid (pHPAA) was measured in 55 children with meningomyelocoele selected at random. In 96% of the children the levels of one or other of these compounds was significantly raised above the normal, usually by a factor of about 3. High VMA levels usually meant high HVA levels but the values for pHPAA appeared to be quite independent of the others. These results suggest a disorder of tyrosine metabolism, and the possible implications are discussed.